CROSS-DISCIPLINARY APPROACH TO PROFESSIONAL TRAINING: INTERNATIONAL EXPERIENCE (Comparative Professional Pedagogy, 2021)
The article considers the peculiarities of cross-disciplinary educational programs in various foreign educational institutions. Emphasis is placed on reforming the education system using a cross-disciplinary model of education in accordance with international standards and labor market requirements. The experience of implementing a cross- disciplinary approach in different specialties has been analyzed. Ways to equalize additional skills that are not provided by educational programs, using a cross-disciplinary approach have been outlined. The importance of using a cross-disciplinary approach as the main part of interdisciplinary studying has been emphasized. The necessity of using cross- disciplinary studying as an integral part of innovative educational techniques has been highlighted. Cross-disciplinarity is described as one of the main integrative teaching methods. Clear definitions of concepts of cross-disciplinarity, multidisciplinarity, and transdisciplinarity have been given. Cross-disciplinary approaches in educational programs at Brown University (Rhode Island, USA), Warren Alpert Medical School of Brown University (Rhode Island, USA), Vienna University of Applied Arts (Universität für angewandte Wunst Wienst), IT University of Copenhagen (Copenhagen, Denmark), Hong Kong University of Science and Technology (Guangzhou), Roberts Wesleyan College (Rochester, NY), Harvard Graduate School of Education (Cambridge, MA) have been analyzed. Special attention has been paid to the Scholarly Concentrations program; a long- term mentoring program based on cross-disciplinary approach that covers all four years of study at Alpert Medical School. It is an optional element of the curriculum that provides students with additional opportunities to develop the skills and abilities through research, scientific and extracurricular experience in one of the twelve areas of science concentration.
Keywords: cross-disciplinarity; interdisciplinarity; cross-disciplinary programs; cross-disciplinary approach; cross-disciplinary training